The Prediction of Mortality Using APACHE II Score in Patients Presenting with Peritonitis and Undergoing Emergency Exploratory Laparotomy - Ashfaq, Hira; Ahmed, Raheel; Dileep Kumar; Kazim, Erum; Dastagir, Sundas; Gul, Aisha (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To Predict mortality using the APACHE II score in patients presenting with peritonitis and undergoing emergency exploratory laparotomy. Methodology: The prospective study was conducted in Civil Hospital Karachi's surgery department from April to September 2021, with a non-probability sampling technique. A total of 84 patients of either sex between the age of 16-70 years who met the diagnostic criteria of peritonitis were included consecutively. Patients with incomplete laboratory records and uncorrectable preoperative comorbidities were excluded. The APACHE II score was categorized into three groups, and demographic details and outcomes were calculated using SPSS version 20 for the data analysis. Post-stratification Chi-square test was applied, taking a p-value of < 0.05 as statistically significant. RESULTS: Out of 84 patients, 38 (45.2%), 37 (44%) and 09 (10.7%) had APACHE score < 10, 11-20 and ? 20 respectively. The total in-hospital mortality rate was 8.3%. In the patients with the lowest APACHE score < 10, a mortality rate of 2.6% was recorded. A mortality of 5.4% was recorded in patients with APACHE II group 2, while group 3 with APACHE II score > 20 had the highest mortality rate of 44%. The difference was statistically significant. (p=0.001). CONCLUSION: The results of the APACHE II score obtained in patients classified them into three different groups based on the severity of conditions in patients with peritonitis, which validated the Prediction of increased mortality with higher scores.